An assessment of the effectiveness of the consumer rights protection strategies in Zimbabwe, Masvingo: A case study of Consumer Council of Zimbabwe - Chikondowa, Pamella (2017)
The major objective of this research was to assess the effectiveness of consumer rights protection strategies used by CCZ in Zimbabwe. The other objectives were to identify consumer rights awarded to consumers, strategies used to protect consumer rights, exploring the challenges faced by CCZ in protecting consumer rights and proffer recommendations to enhance consumer protection in Zimbabwe. The literature reviewed showed that there is much information about reasons leading to establishment of consumer rights and consumer rights protection strategies. This information then lays foundation as the researcher seek to assess how effective then are the strategies used to protect consumer rights. Qualitative and quantitative research designs were employed. On presenting data, graphs, tables and pie charts were used. The findings depicted that consumers have eight rights and consumer education, complaints handling and lobbying and advocacy are strategies used by CCZ to protect these consumer rights. The strategies used by CCZ were labelled ineffective highlighting issues like failure to lobby for a comprehensive consumer act, often referring cases to Small Claims Court, issues to do with accessing consumer education programs and consumer offices especially those in areas far from the major towns. The challenges that undermine CCZ effectiveness and efficiency was largely attributed to governments’ failure to adequately fund the organisation, put in a legal framework inform of consumer act to back consumer rights although other problems were blamed on CCZ itself and consumer themselves. In this light the solutions to enhance consumer protection were directed to government, CCZ and consumers. The researcher concluded that CCZ consumer rights protection strategies are ineffective and this was explained by absence of comprehensive consumer protection act and digital consumer legislations to cope with ever-changing technological environment despite CCZ being in existence for thirty one years, centralization of consumer awareness programs and campaigns as well as CCZ oftenly referring cases to other consumer protection agencies notably the Small Claims Court.